Operation and control of a DVR in the presence of interharmonics - Jindal, A.; Ghosh, Arindam; joshi, A. (Walter de Gruyter GmbH, 2008)
The paper discusses the operating principles and control characteristics of a dynamic voltagerestorer (DVR). It is assumed that the source voltages contain interharmonic components inaddition to fundamental components. The main aim of the DVR is to produce a set of cleanbalanced sinusoidal voltages across the load terminals irrespective of unbalance, distortion andvoltage sag/swell in the supply voltage. An algorithm has been discussed for extractingfundamental phasor sequence components from the samples of three-phase voltages or currentwaveforms having integer harmonics and interharmonics. The DVR operation based on extractedcomponents is demonstrated. The switching signal is generated using a deadbeat controller. It hasbeen shown that the DVR is able to compensate these interharmonic components such that theload voltages are perfectly regulated. The DVR operation under deep voltage sag is also discussed.The proposed DVR operation is verified through the computer simulation studies using theMATLAB software package.